A práxis diaconal como resposta cristã à epidemia de HIV/AIDS - Aguiar, Rogério Oliveira de (2013)
The objective of the present study was to describe the diaconal practice as a Christian activity of care and transformation of a reality that stigmatizes people living with the HIV/AIDS. With that purpose, we analyzed the work developed by the Capuchin Friars at Casa Fonte Colombo (Centre for the Support of HIV Soropositive People) in the city of Porto Alegre, state of Rio Grande do Sul, Brazil. This work is analyzed based on five specific pillars: prevention, welcome, restructuring of family ties, social reintegration, and advocacy. Based on the services provided by Casa Fonte Colombo, the present study was aimed at describing the diakonia considering its different dimensions: prophetic, liberating and political, properly grounded on biblical and theological foundations. The concept of liberation is presented as opposed to the situation of vulnerability imposed by an oppressive system and it is based on a theology focused on the support of stigmatized and socially excluded people. The diaconal practice is presented as opposed to the theologies based on conservative and fundamentalist interpretations of biblical texts, blaming and stigmatizing people living with the HIV/AIDS. The actions described in the present study suggest that solidarity is a concrete response to God's love for humanity; these are prophetic, reconciling, liberating, and thus diaconal actions.